Assessing the performance of the pilot national parks in China. (December 2022) - Zang, Zhenhua; Guo, Zhiqiang; Fan, Xinyue; Han, Mei; Du, Ao; Xu, Weihua; Ouyang, Zhiyun
Graphical abstract: Highlights: Representativeness and management effectiveness of China's pilot national parks was assessed. Representativeness increased by >50 % on average than the existing protected areas. Ten pilot national parks integrated 142 existing protected areas of seven categories. The protected areas and the area under strict protection increased by 19.4% and 42.1%. Relocation and enhanced land management in the pilot NPs reduced human disturbance. Abstract: The continuous decline of global biodiversity highlights the need for the expansion and improved performance of protected areas (PAs) to achieve the Post-2020 Biodiversity Targets and 2030 Sustainable Development Goals. China proposed the establishment of a national park (NP) system and carried out transformative explorations in 10 pilot NPs, however, it is unclear to what extent the pilot NPs represent China's biodiversity and resolve management issues. To answer this question, we assessed the performance of the pilot NPs by analyzing the representativeness across typical ecosystems, biodiversity priority areas, and ecosystem services, and by analyzing the management effectiveness of reorganizing the existing PAs and improving the management intensity and man-land relationships. We found that China's pilot NPs achieved improved representativeness and management effectiveness through range expansion and optimization, institution streamlining, and cohesive management. Compared with the existing PAs, the area of protected typical ecosystems, biodiversity priority areas, and key areas of ecosystem services in the 10 pilot NPs increased by 59.6%, 59.6%, and 54.1% on average, respectively, with a similar land cost overall. The 10 pilot NPs integrated 142 existing PAs of seven categories. The protected areas expanded by 19.4%, and the area under strict protection increased by 42.1%. Additionally, the pilot NPs effectively reduced human disturbance and improved management effectiveness through necessary relocation and enhanced land management. Moving forward, the boundaries and zoning of the NPs should be further optimized, and efforts should be directed to strengthen the governing capacity building, improve the legislation system, increase the financing investment, and promote the value realization of ecological products.